Health promotion and disease prevention registries in the EU: a cross country comparison - Christin Rossmann; Sandra Radoš Krnel; Marika Kylänen; Katarzyna Lewtak; Claudio Tortone; Paola Ragazzoni; Mara Grasso; Alison Maassen; Luciana Costa; Djoeke van Dale (BMC, 2023)
Abstract Background Health promotion and disease prevention programme registries (HPPRs), also called 'best practice portals', serve as entry points and practical repositories that provide decision-makers with easy access to (evidence-based) practices. However, there is limited knowledge of differences or overlaps of howe current national HPPRs in Europe function, the context and circumstances in which these HPPRs were developed, and the mechanisms utilised by each HPPR for the assessment, classification and quality improvement of the included practices. This study prepared an overview of different approaches in several national HPPRs and the EU Best Practice Portal (EU BPP) as well as identified commonalities and differences among the core characteristics of the HPPRs. Methods We conducted a descriptive comparison - that focused on six European countries with existing or recently developed/implemented national HPPR and the EU BPP -to create a comparative overview. We used coding mechanisms to identify commonalities and differences; we performed data management, collection and building consensus during EuroHealthNet Thematic Working Group meetings. Results All HPPRs offer a broad range of health promotion and disease-prevention practices and serve to support practitioners, policymakers and researchers in selecting practices. Almost all HPPRs have an assessment process in place or planned, requiring the application of assessment criteria that differ among the HPPRs. While all HPPRs collect and share recommendable practices, others have implemented further measures to improve the quality of the submitted practices. Different dissemination tools and strategies are employed to promote the use of the HPPRs, including social media, newsletters and publications as well as capacity building workshops for practice owners or technical options to connect citizens/patients with local practices. Conclusions Collaboration between HPPRs (at national and EU level) is appreciated, especially regarding the use consistent terminology to avoid misinterpretation, facilitate cross-country comparison and enable discussions on the adaption of assessment criteria by national HPPRs. Greater efforts are needed to promote the actual implementation and transfer of practices at the national level to address public health challenges with proven and effective practices.